Well-Differentiated Extraskeletal Osteosarcoma Arising from the Retroperitoneum That Recurred as Anaplastic Spindle Cell Sarcoma - Hiromasa Arai; Yasushi Rino; Teppei Nishii; Norio Yukawa; Nobuyuki Wada; Hisashi Oshiro; Tsuyoshi Ishida; Noboru Nakaigawa; Munetaka Masuda (Case Reports in Medicine)
Extraskeletal osteosarcoma is an uncommon high-grade malignant soft tissue sarcoma. Well-differentiated extraskeletal osteosarcoma is thought to have a better prognosis than classical extraskeletal osteosarcoma, but dedifferentiation after recurrence has also been reported. We present a case of a primary retroperitoneal extraskeletal osteosarcoma in a 62-year-old Japanese woman. Abdominal CT revealed a large mass with diffuse calcification in the right retroperitoneal space and tumor resection was performed. The histopathological diagnosis was well-differentiated retroperitoneal extraskeletal osteosarcoma. She was followed up by CT every 6 months without adjuvant radiotherapy and chemotherapy for 31 months until anaplastic high-grade spindle cell sarcoma recurred in the retroperitoneum. Our case is the seventh reported description of well-differentiated extraskeletal sarcoma, and the first to arise in the retroperitoneum and recur as an entirely dedifferentiated spindle cell sarcoma.